Chapter Introduzione - Bravi, Luca (Public History of Education. Teorie, esperienze, strumenti, 2022)
The introduction aims at underlining how the Resistance movement has been dealt throughout the political debate hold in republican Italy, summing up how scholastic law deals with the topic. Eventually, it sums up the following parts of the volume.